2008
DOI: 10.1002/pssb.200879600
|View full text |Cite
|
Sign up to set email alerts
|

Optical absorption of boron nitride nanomaterials

Abstract: Optical absorption spectra have been measured for hexagonal boron nitride (h ‐BN), rhombohedral BN (rh ‐BN), and material obtained by laser vaporization of BN target under a nitrogen atmosphere and contained single‐wall BN‐nanotubes. Band gap of the BN materials was found to have a value of 6.0‐6.3 eV. The spectra of h ‐BN and vaporized material exhibited a peak at ∼5.5 eV, moreover, the latter sample showed an absorption band around 4.5 eV. The vaporized material has been fractionated to the BN‐platelets and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…The absorption coefficient α ( E ) can be calculated as a function of photon energy, E , from the optical constants and, as shown in the inset of Fig. 2(e) , is characterized by a sharp absorption edge at ~6 eV with no lower energy absorption bands resulting from point defects such as N vacancies and C incorporation 39 44 , indicative of a layer with low defect density. Recently, it was reported that hBN is in fact an indirect bandgap semiconductor and the interband optical transition is phonon-assisted 45 .…”
Section: Resultsmentioning
confidence: 99%
“…The absorption coefficient α ( E ) can be calculated as a function of photon energy, E , from the optical constants and, as shown in the inset of Fig. 2(e) , is characterized by a sharp absorption edge at ~6 eV with no lower energy absorption bands resulting from point defects such as N vacancies and C incorporation 39 44 , indicative of a layer with low defect density. Recently, it was reported that hBN is in fact an indirect bandgap semiconductor and the interband optical transition is phonon-assisted 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the optical absorption bands with the same energies were observed in the spectrum of thin BN platelets16 …”
mentioning
confidence: 62%
“…Compared to novel materials such as graphene, BP, and TMDCs, BN, is a traditional 2D nano‐sheet material with a band gap of 0.3–6 eV. BN has been a highly attractive material in various fields for many years as a result of its properties which include low abrasion, fire resistance, a low dielectric constant, low dielectric loss, high thermal conductivity, and resistance to corrosion and oxidation . However, the optical characteristics of BN have not been fully reported, with only some studies investigating the optical absorption from the BN material.…”
Section: Comparisons Of Passively Mode‐locked 2 µM Laser Performance mentioning
confidence: 99%
“…BN has been a highly attractive material in various fields for many years as a result of its properties which include low abrasion, fire resistance, a low dielectric constant, low dielectric loss, high thermal conductivity, and resistance to corrosion and oxidation. [26][27][28][29] However, the optical characteristics of BN have not been fully reported, with only some studies investigating the optical absorption from the BN material. Currently, there is no published report on the preparation and application of a BN-based SA for mode-locked lasers.…”
mentioning
confidence: 99%